Risk of SARS‐CoV‐2 infection, hospitalization, and death for COVID‐19 in people with Parkinson disease or parkinsonism over a 15‐month period: A cohort study. (2nd August 2022) - Zenesini, Corrado; Vignatelli, Luca; Belotti, Laura Maria Beatrice; Baccari, Flavia; Calandra‐Buonaura, Giovanna; Cortelli, Pietro; Descovich, Carlo; Giannini, Giulia; Guaraldi, Pietro; Guarino, Maria; Loddo, Giuseppe; Pantieri, Roberta; et al.
Abstract: Background and purpose: The patterns of long‐term risk of SARS‐CoV‐2 infection, hospitalization for COVID‐19, and related death are uncertain in people with Parkinson disease (PD) or parkinsonism (PS). The aim of the study was to quantify these risks compared to a control population cohort, during the period March 2020–May 2021, in Bologna, Northern Italy. Methods: ParkLink Bologna cohort (759 PD, 192 PS) and controls (9226) anonymously matched (ratio = 1:10) for sex, age, district, and comorbidity were included. Data were analysed in the whole period and in the two different pandemic waves (March–May 2020 and October 2020–May 2021). Results: Adjusted hazard ratio of SARS‐CoV‐2 infection was 1.3 (95% confidence interval [CI] = 1.04–1.7) in PD and 1.9 (95% CI = 1.3–2.8) in PS compared to the controls. The trend was detected in both the pandemic waves. Adjusted hazard ratio of hospitalization for COVID‐19 was 1.1 (95% CI = 0.8–1.7) in PD and 1.8 (95% CI = 0.97–3.1) in PS. A higher risk of hospital admission was detected in PS only in the first wave. The 30‐day mortality risk after hospitalization was higher ( p  = 0.048) in PS (58%) than in PD (19%) and controls (26%). Conclusions: Compared with controls, after adjustment for key covariates, people with PD and PS showed a higher risk of SARS‐CoV‐2 infection throughout the first 15 months of the pandemic. COVID‐19 hospitalization risk was increased only in people with PS and only during the first wave. This group of patients was burdened by a very high risk of death after infection and hospitalization. Abstract : Compared with controls, people with Parkinson disease and parkinsonism showed a higher risk of SARS‐CoV‐2 infection throughout the first 15 months of the pandemic. COVID‐19 hospitalization risk was increased only in people with parkinsonism and only during the first wave. This group of patients was burdened by a very high risk of death after infection and hospitalization.